Rise and fall of preoperative coronary revascularization. (3rd May 2020) - Raghunathan, Deepa; Palaskas, Nicolas L.; Yusuf, Syed Wamique; Eagle, Kim A.
ABSTRACT: Introduction: About 234 million major surgical procedures are performed each year worldwide, of which >60 million surgeries are performed in the United States. Though postoperative major adverse cardiac complications are relatively low, patients with postoperative myocardial infarction have higher in-hospital mortality. Thus, comprehensive cardiac evaluations, and in some cases, elective coronary revascularizations, are performed prior to surgery with an intent to minimize these complications. In 2009, approximately 4% of all elective percutaneous coronary interventions were performed in preparation for noncardiac surgery. Areas covered: We discuss relevant articles from the last 50 years regarding elective preoperative coronary revascularization prior to noncardiac surgery. Expert opinion: In the early years there was an interest in preemptive revascularization to reduce postoperative cardiac events; however, subsequent studies in patients with stable coronary artery disease have mostly shown that a strategy of routine prophylactic coronary revascularization prior to noncardiac surgery does not reduce postoperative cardiac complications.